Green Human Resource Management and Competitive Advantage: The Mediating Role of Organizational Commitment in Private Firms - Amir Makhmud Zain Nst; Dian Purnama Sari (Fundamental and Applied Management Journal, 2026)
This study examines the effect of Green Human Resource Management (GHRM) on competitive advantage with organizational commitment as a mediating variable in private firms in Medan, Indonesia. As sustainability becomes a strategic imperative, firms are increasingly integrating environmental principles into their human resource systems to strengthen long-term competitiveness. However, limited empirical evidence explains the internal mechanism linking GHRM to competitive advantage, particularly in emerging economy contexts. This research adopts a quantitative approach using survey data collected from 212 employees of private firms in Medan. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and indirect relationships. The results indicate that GHRM significantly influences organizational commitment (β = 0.68, p < 0.001) and competitive advantage (β = 0.29, p < 0.001). Organizational commitment also significantly affects competitive advantage (β = 0.41, p < 0.001) and partially mediates the relationship between GHRM and competitive advantage. The findings highlight that sustainability-oriented HR practices function as strategic resources that enhance employee attachment and strengthen firm competitiveness. This study contributes to the integration of the Resource-Based View and social exchange theory and provides practical insights for firms seeking to align sustainability initiatives with competitive performance.